The Concept of Tazkiyah an-Nafs Bediuzzaman Said Nursi In Risale-i Nur - Yusrina Dyah Wulandari; Romlah Widyawati; Rochmad; Niken Sylvia Puspitasari (Jurnal test, 2024)
This research stems from bad phenomena in the modern era, namely despicable human behaviour, which results in division and hostility caused by undirected lust. This article aims to examine a discussion to treat this despicable behaviour by doing tazkiyah an-nafs. Because the discussion contains elements of Sufism, the author will analyze the interpretation of tazkiyah an-nafs from Bediuzzaman Said Nursi’s commentary entitled Risale-i Nur. This study uses the library research method, collects library data with the theme “the concept of tazkiyah an-nafs Bediuzzaman said Nursi in Risale-i Nur” and analyzes the verses related to the theme of the commentator. The results of this study illustrate that tazkiyah an-nafs, according to Said, is purifying the soul by protecting the heart and soul from contracting harmful diseases. They are implementing various steps, including increasing faith, worshipping, taking parable from the story of the Prophet, leaving despicable deeds, and doing meritorious deeds.